Adhesive composition, bonded body, and method for producing adhesive composition
Patent Information
- Application Number
- CN202280007060.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-03-23
AI Technical Summary
[0023] According to the present invention, an adhesive composition with good storage stability and high adhesive strength is provided.
Smart Images

Figure BDA0004189591810000051 
Figure BDA0004189591810000061 
Figure BDA0004189591810000141
Abstract
Description
Technical Field
[0001] This invention relates to adhesive compositions, bonding agents, and methods for manufacturing adhesive compositions. Background Technology
[0002] As adhesive compositions, epoxy adhesives, acrylic adhesives, and urethane adhesives are known. Among these, acrylic adhesives generally exhibit superior performance in terms of oil adhesion and workability.
[0003] As an example of an acrylic adhesive, Patent Document 1 can be cited. Patent Document 1 describes an acrylic adhesive composition containing: (1) a (meth)acrylic acid derivative monomer, (2) a polymerization initiator, (3) a reducing agent, and (4) a diene core-shell polymer. In this composition, the diene core-shell polymer is MBS resin (methyl methacrylate-acrylonitrile-butadiene-styrene copolymer), which can swell in the (meth)acrylic acid derivative monomer and has a swelling degree of 9.5 or more in toluene at 25°C.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent No. 4707320 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] The inventors of this application conducted research and, as a result, completed an adhesive composition that exhibits improved storage stability compared to the adhesive composition described in Patent Document 1. Specifically, through this invention, an adhesive composition has been completed that provides the desired adhesive strength even some time after manufacturing.
[0009] Methods for solving problems
[0010] The inventors of this application have completed the inventions provided below.
[0011] According to the present invention, an adhesive composition is provided comprising:
[0012] Polymerizable monomers containing (meth)acryloyl groups;
[0013] Free radical polymerization initiators; and
[0014] Polymer particles that swell due to organic solvents,
[0015] In the particle size distribution of secondary particles, which are aggregates of the aforementioned polymer particles, in the adhesive composition as determined by laser diffraction and scattering, the proportion of secondary particles with a diameter of 1 μm or more but less than 200 μm is 30% by volume or more.
[0016] Additionally, according to the present invention, a coupling body is provided, comprising:
[0017] First structural component;
[0018] Second structural component; and
[0019] The cured form of the adhesive composition described above bonds the first structural component to the second structural component.
[0020] Furthermore, according to the present invention, a method for manufacturing the above-mentioned adhesive composition is provided, comprising a dispersion step of adding the aforementioned polymer particles into a container containing the aforementioned polymeric monomer and stirring to disperse the aforementioned polymer particles in the aforementioned polymeric monomer.
[0021] The temperature of the aforementioned polymeric monomers at the time of input is above 0°C and below 40°C.
[0022] Invention Effects
[0023] According to the present invention, an adhesive composition with good storage stability and high adhesive strength is provided. Detailed Implementation
[0024] The embodiments of the present invention will now be described in detail.
[0025] In this specification, unless otherwise specified, expressions such as "X~Y" in the description of numerical ranges mean X or more and Y or less. For example, "1~5% by mass" means "1% by mass or more and 5% by mass or less".
[0026] In this specification, the dosage is preferably expressed as the amount relative to the total of the first and second doses.
[0027] In the description of groups (atomic groups) in this specification, the description of "unsubstituted" or "unsubstituted" includes both cases with and without substituents. For example, the term "alkyl" includes not only unsubstituted alkyl groups (unsubstituted alkyl groups) but also substituted alkyl groups (substituted alkyl groups).
[0028] The use of terms like "(meth)propylene-" in this specification indicates that both propylene- and methpropylene- are included. The same applies to terms like "(meth)acrylate".
[0029] Unless otherwise specified, the term "organic group" in this specification refers to a group of atoms formed by removing one or more hydrogen atoms from an organic compound. For example, "monovalent organic group" means a group of atoms formed by removing one hydrogen atom from any organic compound.
[0030] <Adhesive Composition>
[0031] The adhesive composition of this embodiment comprises: a polymerizable monomer having (meth)acryloyl groups, a free radical polymerization initiator, and polymer particles having the property of swelling due to organic solvents.
[0032] In the particle size distribution of secondary particles, which are aggregates of the polymer particles, in the adhesive composition of this embodiment, as determined by laser diffraction and scattering, the proportion of secondary particles with a diameter of 1 μm to 200 μm is 30% by volume or more, preferably 40% by volume or more, and more preferably 50% by volume or more. This value can be 100% by volume or 99.5% by volume or less.
[0033] The inventors of this application have conducted various studies to improve the storage stability of adhesive compositions. As described above, the inventors of this application have set the proportion of secondary particles with a diameter of 1 μm to 200 μm to 30% or more in the particle size distribution of the secondary particles that are aggregates of polymer particles. As a result, an adhesive composition with good storage stability and high adhesive strength can be provided.
[0034] The manufacturing method of the adhesive composition of this embodiment is not limited, but from the viewpoint of appropriately controlling the particle size distribution of secondary particles as aggregates of polymer particles, it is preferable to adopt appropriate manufacturing methods and conditions. Key aspects of the manufacturing methods and conditions include, for example, appropriately controlling the temperature during mixing of the polymeric monomer and polymer particles, and the stirring speed (stirring rate) during mixing. Details of the manufacturing methods and conditions will be described later.
[0035] The following will continue to describe the components that may be included in the adhesive composition of this embodiment, the physical properties of the adhesive composition of this embodiment, and other matters related to the adhesive composition of this embodiment.
[0036] (polymerizable monomers)
[0037] The adhesive composition of this embodiment contains a polymerizable monomer having a (meth)acryloyl group. In this specification, the polymerizable monomer having a (meth)acryloyl group is also simply referred to as a "polymerizable monomer".
[0038] Specifically, the following monomers can be cited as examples of polymerizable monomers.
[0039] (i) Monomers represented by the general formula ZO-R1.
[0040] In the general formula, Z represents (meth)acryloyl, CH2=CHCOOCH2CH2-, CH2=C(CH3)COOCH2-CH2CH2-, CH2=CHCOOCH2-CH(OH)-, CH2=C(CH3)COOCH2-CH(OH)-, CH2=CHCOOCH2-CH(OH)CH2- or CH2=C(CH3)COOCH2-CH(OH)CH2-, and R1 represents hydrogen, alkyl, cycloalkyl, benzyl, phenyl, tetrahydrofurfuryl, glycidyl, dicyclopentyl, dicyclopentenyl, (meth)acryloyl, and isobornyl.
[0041] Examples of such monomers include methyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, tetrahydrofurfuryl methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, glycerol (meth)acrylate, glycerol di(meth)acrylate, isobornyl methacrylate, and methacrylic acid.
[0042] (ii) General formula ZO-(R2O) p -R1 represents the monomer.
[0043] In the general formula, Z and R1 are as described above. R2 represents -C2H4-, -C3H6-, -CH2CH(CH3)-, -C4H8-, or -C6H 12 -, p represents an integer greater than 1 and less than 25.
[0044] Examples of such monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, ethoxyethyl (meth)acrylate, polyethylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and phenoxydiethylene glycol (meth)acrylate.
[0045] (iii) General formula
[0046] [Chemical Formula 1]
[0047]
[0048] The monomer represented.
[0049] In the general formula, Z and R2 are as described above. R3 represents hydrogen or an alkyl group with 1 to 4 carbon atoms, and q represents an integer from 0 to 8. Z, R2, R3, and q can be the same or different.
[0050] Examples of such monomers include 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, and ethoxylated bisphenol A di(meth)acrylate.
[0051] (iv) (meth)acrylates of polyols not included in (i), (ii) or (iii) above.
[0052] Examples of such monomers include trimethylolpropane tri(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripropylene glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0053] (v) Carbamate prepolymers having (meth)acryloyloxy groups. Such monomers can be obtained, for example, by reacting hydroxyl-containing (meth)acrylates, organic polyisocyanates, and polyols.
[0054] Examples of (meth)acrylates having hydroxyl groups include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate.
[0055] Examples of organic polyisocyanates include, for example, toluene diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
[0056] Examples of polyols include polyethylene glycol, polypropylene glycol, polybutane glycol, and polyester polyols.
[0057] (vi) Acidic phosphoric acid compounds represented by general formula (I).
[0058] [Chemical Formula 2]
[0059] General Formula (I)
[0060]
[0061] In the above general formula, R represents CH2=CR4CO(OR5) m - group (where R4 represents hydrogen or methyl, and R5 represents -C2H4-, -C3H6-, -CH2CH(CH3)-, -C4H8-, -C6H-). 12 -or-C2H4-OCO-C5H 10-, m represents an integer greater than 1 and less than 10. ), n represents an integer of 1 or 2.
[0062] Examples of acidic phosphoric acid compounds represented by general formula (I) include (meth)acrylic acid phosphoryl oxyethyl ester, (meth)acrylic acid phosphoryl oxypropyl ester, bis(2-(meth)acryloyloxyethyl) phosphate, 2-(meth)acryloyloxyethyl acid phosphate, etc.
[0063] The preferred polymerizable monomers (monofunctional and polyfunctional) are the following monomers.
[0064] Monofunctional
[0065] Methyl methacrylate, ethylhexyl methacrylate, lauryl methacrylate, ethylene oxide-modified nonylphenol (meth)acrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, dicyclopentenyloxyethyl methacrylate, dicyclopentyloxyethyl methacrylate, cyclohexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and methacrylate
[0066] Multisensory
[0067] Ethylene oxide-modified di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and ethoxylated pentaerythritol tetra(meth)acrylate
[0068] The adhesive composition of this embodiment may contain only one of the monomers (i) to (vi), or it may contain two or more of them. Among these, from the viewpoint of having high adhesiveness and low adhesive strain on the bonded objects, it is preferable to have one or more of (i), (ii) and (vi), and more preferably to use (i), (ii) and (vi) together.
[0069] When using (i) and (ii), the composition ratio by mass is preferably (i):(ii) = 50–95:5–50, more preferably 60–80:20–40. When using (vi), the amount used is preferably 0.05 to 10 parts by mass relative to a total of 100 parts by mass of (i) and (ii), more preferably 0.1 to 5 parts by mass.
[0070] (Free radical polymerization initiator)
[0071] The adhesive composition of this embodiment includes a free radical polymerization initiator. By using the free radical polymerization initiator to polymerize the polymerizable carbon-carbon double bonds of the monomers, adhesion of articles can be achieved.
[0072] As a free radical polymerization initiator, a thermal free radical polymerization initiator is preferred. Organic peroxides are preferred examples of thermal free radical polymerization initiators. Examples of organic peroxides include cumene hydroperoxide, p-menthol hydroperoxide, tert-butyl hydroperoxide, dicumene hydroperoxide, methyl ethyl ketone peroxide, tert-butyl peroxide, and benzoyl peroxide. Among these, cumene hydroperoxide is preferred from a stability perspective.
[0073] Incidentally, by using a free radical polymerization initiator and a reducing agent (described later), curability can be further improved, or room temperature curing can be achieved.
[0074] The amount of free radical polymerization initiator is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the polymerizable monomer, more preferably 0.4 to 10 parts by mass. By using a moderately large amount of free radical polymerization initiator, the curing speed can be sufficiently accelerated. On the other hand, by ensuring that the amount of free radical polymerization initiator is not excessive, storage stability can be further improved.
[0075] (polymer particles)
[0076] The adhesive composition of this embodiment comprises polymer particles that swell due to organic solvents. "Swelling due to organic solvents" means that the polymer particles absorb the liquid and swell when in contact with a liquid such as an organic solvent. Specifically, the degree of swelling is preferably 5 times or more, more preferably 7 times or more, further preferably 9.5 times or more, and particularly preferably 10 times or more. The upper limit of the degree of swelling is, for example, 15 times.
[0077] The degree of swelling can be determined as described in paragraph 0049 of the aforementioned Patent Document 1. Specifically, 1 g of sample is placed in 100 mL of toluene at 25°C and allowed to stand for 24 hours. The swollen gel in the toluene is then filtered through a 100-mesh metal mesh (mass A). After 1 minute, the mass B of the swollen gel and the metal mesh is measured. The sample is then air-dried at room temperature for 24 hours, followed by vacuum drying. The mass C of the dried gel and the metal mesh is then measured. The degree of swelling (times) can then be calculated using the formula: (BA) / (CA).
[0078] By making the polymer particles swellable, polymerizable monomers enter the polymer particles and polymerize within them, resulting in an expected improvement in bond strength and other properties.
[0079] In this specification, polymer particles that have the property of swelling due to organic solvents are also simply referred to as "polymer particles".
[0080] For clarity, the following statements are made. Unless otherwise specified, the various particle sizes of polymer particles and the numerical values related to particle size distribution in this specification refer to the numerical values of polymer particles in the adhesive composition (in the case of swollen polymer particles, the particle size in the swollen state, etc.).
[0081] As a point of view, the polymer particles preferably include core-shell polymer particles. Core-shell polymer particles can be obtained by methods described in International Publication No. 2005 / 028546, Japanese Patent Application Publication No. 2016-104834, etc.
[0082] As another viewpoint, the polymer particles preferably comprise diene-based polymers, and more preferably, the polymers constituting the polymer particles comprise (meth)acrylonitrile-butadiene-styrene copolymers, and / or (meth)acrylate-(meth)acrylonitrile-butadiene-styrene copolymers.
[0083] The median particle size D of the secondary particles is determined based on the particle size distribution of the secondary particles. 50 Preferably, the micrometer size is 1 μm or more and 200 μm or less, more preferably 5 μm or more and 180 μm or less, and even more preferably 10 μm or more and 150 μm or less.
[0084] The cumulative 90% diameter D of the secondary particles was calculated based on the particle size distribution of the secondary particles. 90 Preferably, the micrometer size is 10μm or more and 500μm or less, more preferably 20μm or more and 400μm or less, and even more preferably 30μm or more and 300μm or less.
[0085] From the perspective of a different proportion of secondary particles with diameters between 1 μm and 200 μm, as mentioned above, these values specify a lower proportion of coarse secondary particles. By adjusting these values, the performance of the adhesive composition can be further improved.
[0086] Median particle size D of secondary particles 50 And the cumulative 90% diameter D of secondary particles 90 The adjustment can be achieved, for example, by appropriately controlling the temperature during mixing of the polymeric monomer and polymer particles, and the shear force during mixing. The shear force can be adjusted, for example, by appropriately selecting the rotational speed of the stirring blades, the diameter of the stirring blades, and the stirring speed (stirring speed).
[0087] Incidentally, the volume average particle size of the "primary particles" of the polymer particles is preferably 0.01 μm to 1 μm, more preferably 0.02 μm to 0.8 μm, and even more preferably 0.03 μm to 0.6 μm. By appropriately selecting the volume average particle size of the primary particles, the performance of the adhesive composition can be further improved.
[0088] For example, the volume average particle size of the primary particles can be adjusted by performing a pulverizing process on the polymer particles and a sieving process after pulverization. The volume average particle size of the primary particles can also be adjusted by using polymer particles with a suitable particle size distribution.
[0089] The polymer particles that can be used are preferably obtained from Denka Co., Ltd. and Kaneka Co., Ltd.
[0090] The amount of polymer particles is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of polymeric monomer, more preferably 1 to 20 parts by mass. By using a moderate amount of polymer particles, the toughness of the cured film can be further improved. On the other hand, by keeping the amount of polymer particles not too high, sufficient amounts of polymeric monomer and polymerization initiator can be used, tending to further improve the curability.
[0091] (elastomer)
[0092] The adhesive composition of this embodiment preferably contains one or more elastomers. The elastomers preferably do not include the aforementioned polymer particles. By using elastomers, the cured adhesive composition exhibits moderate elasticity, enabling, for example, further improvements in toughness.
[0093] Examples of elastomer components include (meth)acrylonitrile-butadiene-(meth)acrylic acid copolymer, (meth)acrylonitrile-butadiene-(meth)acrylate copolymer, (meth)acrylonitrile-butadiene copolymer, styrene-butadiene copolymer, chlorosulfonated polyethylene, styrene-polybutadiene-styrene synthetic rubber, and polybutadiene and urethane elastomers with (meth)acrylic acid modified ends.
[0094] From the perspective of solubility and adhesion, it is preferable to select one or more from the group consisting of (meth)acrylonitrile-butadiene-(meth)acrylic acid copolymer and (meth)acrylonitrile-butadiene copolymer (NBR, etc.).
[0095] When using an elastomer, its amount relative to 100 parts by mass of the polymeric monomer, calculated as a total of polymer particles, is preferably 5 to 40 parts by mass, more preferably 10 to 30 parts by mass.
[0096] (reducing agent)
[0097] The adhesive composition of this embodiment preferably contains one or more reducing agents. By using a free radical polymerization initiator and a reducing agent together, curability can be further improved, or room temperature curing can be achieved.
[0098] The reducing agent can be any known reducing agent that reacts with the polymerization initiator to generate free radicals. Preferably, the reducing agent is selected from at least one of the group consisting of tertiary amines, thiourea derivatives, and transition metal salts, more preferably a transition metal salt. Examples of thiourea derivatives include acetylthiourea and ethylenethiourea. Examples of transition metal salts include cobalt naphthenate, cobalt octoate, copper naphthenate, and vanadium acetylacetonate. Among transition metal salts, vanadium acetylacetonate is preferred.
[0099] When using a reducing agent, the amount used is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymerizable monomer, more preferably 0.1 to 5 parts by mass. By using 0.01 parts by mass or more, the curing speed is sufficiently accelerated, and by setting it to 10 parts by mass or less, the storage stability becomes better.
[0100] (paraffin)
[0101] The adhesive composition of this embodiment may contain paraffin wax. Specifically, various types of paraffin wax can be used to ensure rapid curing of the parts exposed to air. Examples of paraffin wax include solid paraffin wax, microcrystalline wax, carnauba wax, beeswax, lanolin, cetacean wax, ceresin wax, and candelilla wax.
[0102] When the adhesive composition of this embodiment contains paraffin, it may contain only one type of paraffin or two or more types of paraffin.
[0103] When the adhesive composition of this embodiment contains paraffin, the amount of paraffin is preferably 0.01 parts by mass or more than 3 parts by mass, and more preferably 0.5 parts by mass or more than 2 parts by mass, relative to 100 parts by mass of the polymerizable monomer. By using a sufficiently large amount of paraffin, the effect of rapid curing can be sufficiently obtained. On the other hand, by keeping the amount of paraffin not excessive, the effect of rapid curing can be obtained while obtaining sufficient adhesion.
[0104] (Other ingredients)
[0105] The adhesive composition of this embodiment may contain any components other than those described above, or may not contain any components at all.
[0106] As an example, in order to adjust the film thickness during use, the adhesive composition of this embodiment may include spacers (particles). Typically, the spacers are spherical particles made of resins such as polyolefins.
[0107] As another example, to improve storage stability (suppress deterioration during storage), the adhesive composition of this embodiment may contain various stabilizers. Examples of stabilizers include: (i) compounds known as phenolic antioxidants; (ii) quinone compounds, such as p-benzoquinone, hydroquinone monomethyl ether, etc.; (iii) compounds known as polymerization inhibitors, such as amine polymerization inhibitors like phenothiazine; (iv) stable radical-type compounds having stable free radicals; and so on. Among these, stable radical-type compounds are preferred from the perspective of improving storage stability without impairing the properties of the adhesive (tensile shear bond strength, storage modulus).
[0108] As a stable free radical, a nitroxide free radical is preferred. Specifically, examples of stable free radical compounds that are nitroxide free radicals include 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxyl-2,2,6,6-tetramethylpiperidine-1-oxyl, and 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl. When using stable free radical compounds, it is preferable to use one or more of these.
[0109] When using stabilizers such as stable free radical compounds, the content of these stabilizers, in order to improve storage stability without impairing their performance as adhesives, is, for example, 0.001 parts by mass or less and 1 part by mass or less, preferably 0.001 parts by mass or less and 0.5 parts by mass or less, more preferably 0.01 parts by mass or less and 0.3 parts by mass or less, and even more preferably 0.02 parts by mass or less and 0.1 parts by mass or less, relative to 100 parts by mass of the polymerizable monomer.
[0110] (Single-dose form / Two-dose form)
[0111] The adhesive composition of this embodiment can be either a so-called one-component or a two-component (an adhesive composition in which two reagents filled in different containers are mixed before use).
[0112] In the case of a two-component formulation, preferably, the free radical polymerization initiator is contained in the first component, and the reducing agent is contained in the second component. Preferably, a tertiary amine is contained in the first component, and a thiourea derivative or transition metal salt is contained in the second component. Other components may be appropriately mixed in the two components. The first and second components are mixed before use.
[0113] Incidentally, when the adhesive composition of this embodiment is a two-component form, it is preferable to adjust the amount of each component in the first and second agents so that the adhesive composition after mixing the first and second agents contains each component within the appropriate content range of the above-mentioned components.
[0114] <Method for manufacturing adhesive composition>
[0115] The method for manufacturing the adhesive composition of this embodiment is not limited. However, from the viewpoint of appropriately controlling the particle size distribution of secondary particles as aggregates of polymer particles, it is preferable to employ appropriate manufacturing methods and conditions. As key aspects of the manufacturing method and conditions, for example, appropriate control of the temperature during mixing of the polymeric monomer and the polymer particles, and the stirring speed during mixing, can be cited.
[0116] The method for manufacturing the adhesive composition of this embodiment preferably includes a dispersion step of adding polymer particles into a container containing polymeric monomers and stirring to disperse the polymer particles in the polymeric monomers. In this dispersion step, the temperature of the polymeric monomers in the container when the polymer particles are added is preferably 0°C to 40°C, more preferably 15°C to 35°C.
[0117] By ensuring that the temperature of the polymerizing monomer is above 0°C when the polymer particles are introduced, the polymer particles can be easily dispersed in the polymerizing monomer in a shorter time.
[0118] In addition, by keeping the temperature of the polymerizable monomers below 40°C during addition, it is less likely to form clumps (agglomerates, powder agglomerates) of polymer particles, thus making it easier to obtain a good polymer dispersion state.
[0119] The dispersion process preferably uses stirring blades to mix the polymeric monomers and polymer particles. To ensure the polymer particles are sufficiently and uniformly dispersed within the polymeric monomers, the stirring speed of the stirring blades is preferably 300 mm / s or higher, more preferably 500 mm / s or higher. There is no particular upper limit to the stirring speed, but due to equipment limitations, it may be, for example, 300,000 mm / s or lower.
[0120] <Uses of Adhesive Compositions / Joints>
[0121] By applying the adhesive composition of this embodiment to an article and curing it, a bonded body comprising a cured body of the adhesive composition can be obtained. Specifically, by using the adhesive composition of this embodiment, a bonded body comprising a first structural member, a second structural member, and a cured body of the adhesive composition that bonds the first structural member and the second structural member can be obtained.
[0122] Especially when the adhesive composition of this embodiment contains a reducing agent, it is preferable that the articles can be bonded even without heating (at room temperature). Of course, heating is not excluded when the bonded body is obtained.
[0123] The embodiments of the present invention have been described above, but these are merely examples, and various configurations other than those described can be employed. Furthermore, the present invention is not limited to the embodiments described above, and modifications and alterations within the scope of achieving the objectives of the present invention are included in the present invention.
[0124] Example
[0125] The embodiments of the present invention will be described in detail based on examples and comparative examples. The following statements are made for clarity, but the present invention is not limited to the embodiments.
[0126] <Preparation of Adhesive Compositions>
[0127] Agent A (Agent 1) and Agent B (Agent 2) of each embodiment and comparative example were manufactured in the following manner.
[0128] (1) Add the monomers (unit: parts by mass, the same applies to other components) listed in the table below “Polymerizable Monomers” and the NBR listed in “Elastomers” to a temperature-adjustable mixing container, and stir and mix at 60°C for 1 hour using a stirring blade (anchoring wing).
[0129] (2) Add the polymer particles listed in the "Polymer Particles" section of the table below into the container. The temperature at which the polymer particles are added is shown in the table below. Then, mix for 1 hour using a stirring blade. The stirring speed, blade diameter, and stirring circumferential speed are as shown in the table.
[0130] (3) Add the remaining ingredients into the container and stir at room temperature for 24 hours to mix thoroughly.
[0131] In the tables described below, for polymerizable monomers, free radical polymerization initiators, reducing agents and 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxo radicals, use commercially available substances as appropriate.
[0132] Details of the polymer particles and elastomers are shown below.
[0133] Product 1: Core-shell particles, methyl methacrylate-acrylonitrile-butadiene-styrene copolymer, swelling degree measured in accordance with the method described in paragraph 0049 of Patent Document 1: 14.0. Product 2: Core-shell particles, acrylonitrile-butadiene-styrene copolymer, swelling degree measured in accordance with the method described in paragraph 0049 of Patent Document 1: 10.1.
[0134] NBR: JSR Corporation's "230S" (bonded acrylonitrile content: 35%, Mooney viscosity: 56)
[0135] The structure of ethoxylated bisphenol A dimethacrylate is shown below.
[0136] [Chemical Formula 3]
[0137]
[0138] <Determination of Particle Size Distribution of Polymer Particles in Adhesive Compositions>
[0139] Perform the measurement according to the following steps.
[0140] (1) Take 1g of adhesive composition into a 10mL glass tube bottle and add 4g of methyl methacrylate (manufactured by Tokyo Chemical Industry, >99.8%) (methyl methacrylate is used to facilitate the determination of particle size distribution by diluting the composition).
[0141] (2) Cover the glass tubular bottle and let it stand at 23°C for 24 hours without shaking. Use a dropper to take out the supernatant from the glass tubular bottle after standing, and determine the particle size distribution of the polymer particles contained in the supernatant. For the determination of particle size distribution, it was carried out according to JIS Z 8825:2013 using the Shimadzu SALD-2200 laser diffraction particle size distribution measuring device at a measurement temperature of 23°C and a measurement solvent of methyl methacrylate (Tokyo Chemical Industry Co., Ltd., >99.8%).
[0142] (3) Based on the measurement results, the following values are obtained.
[0143] • The proportion of secondary particles with diameters between 1 μm and 200 μm in the particle size distribution of secondary particles.
[0144] • Median particle size D of secondary particles 50
[0145] • 90% of the cumulative secondary particles are diameter D 90
[0146] To clarify, in typical particle size distribution measurements, ultrasonic dispersion or similar methods are used to minimize secondary particles. However, in this study, to obtain information on the particle size distribution of the adhesive composition reflecting the aggregation state of polymer particles, ultrasonic dispersion or other dispersion treatments were not performed; instead, only dilution with methyl methacrylate was conducted.
[0147] <Determination of particle size distribution of polymer particles themselves (primary particles)>
[0148] Determine using the following steps.
[0149] (1) Take 0.1g of polymer particles (product 1 or product 2) into a 10mL glass tube bottle, add 4.9g of 0.2% by mass sodium hexametaphosphate aqueous solution, and disperse it using ultrasound (130W) for 10 minutes.
[0150] (2) The particle size distribution of the polymer particles contained in the dispersion was determined. For the determination of particle size distribution, the determination was carried out in accordance with JIS Z 8825:2013 using the Shimadzu SALD-2200 laser diffraction particle size distribution measuring device at a measurement temperature of 23°C and a measurement solvent of pure water.
[0151] (3) In the measurement results, the volume average particle size of the primary particles of the polymer particles is set as the measurement result.
[0152] <Determination and Evaluation of Viscosity>
[0153] According to JIS K 6838, the viscosity (unit: mPa·s) of each adhesive composition (agent A, agent B) was measured using a type B viscometer at a rotor speed of 20 rpm, a measurement time of 2 minutes, and a measurement atmosphere temperature of 25°C. This measured viscosity value is designated as A1. It should be noted that for each adhesive composition (agent A, agent B), it should be allowed to stand at 25°C for at least 24 hours before measurement, adjusting the liquid temperature to 25°C.
[0154] Next, each adhesive composition (A agent and B agent) was filled into a 500mL polyethylene bottle at a dose of 500g and allowed to stand at 23°C for one week. Then, the viscosity of A agent and B agent after standing was measured using the same method. This viscosity measurement value is set as A2. Then, the viscosity retention rate A (%) is calculated using the following formula.
[0155] A(%)=(A2 / A1)×100
[0156] In addition, regarding viscosity, the thixotropic index (TI) was also measured. Specifically, TI was calculated by dividing A1 by A1' and obtaining the viscosity A1', which was measured in the same manner as the A1 measurement except that the rotation speed was changed from 20 rpm to 2 rpm.
[0157] <Evaluation of Adhesion Toughness>
[0158] The evaluation was conducted in accordance with JIS K 6854 as follows. The evaluation was carried out at an environment of 23°C and 50% relative humidity.
[0159] First, prepare a mixture of equal amounts of agent A and agent B from the adhesive compositions of each embodiment and comparative example. Quickly apply this mixture to one side of a test piece (200mm × 25mm × 1.6mm, SECC steel plate). Immediately stack another test piece (200mm × 25mm × 0.5mm: SECC steel plate) on top and secure it with clips. Then, cure at room temperature for 24 hours. Evaluation samples are obtained in this manner.
[0160] Using the obtained evaluation samples, the peel strength (peel strength, unit: kN / m) was measured. The peel strength (unit: kN / m) was measured at a tensile speed of 50 mm / min under conditions of 23°C and 50% relative humidity. Three measurements were performed, and the average value was recorded as the peel strength in the table. The standard deviation of the three measurements is also recorded in the table. Furthermore, the results obtained from observing the failure state are also recorded in the table. In the failure state, the area ratio of the failure type was calculated. Generally, high bond strength is obtained in cases of cohesive failure; therefore, cohesive failure is preferred among the failure states.
[0161] The above information is summarized in the table below. The amounts of polymerizable monomers, polymer particles, elastomers, free radical polymerization initiators, reducing agents, and other components are expressed in parts by mass.
[0162] [Table 1]
[0163]
[0164] As shown in the table above, the viscosity retention rate (A) of adhesive compositions with a polymer particle diameter of 1 μm to 200 μm or more exceeding 30% by volume is almost 100%. That is, it exhibits good storage stability.
[0165] Furthermore, by using an adhesive composition in which the proportion of secondary particles with a diameter of 1 μm to 200 μm is 30% or more by volume, SECC steel sheets can be firmly bonded to each other. That is, high adhesive strength can be obtained.
[0166] The inventors of this application conducted various studies to improve the storage stability of adhesive compositions. Through these studies, it was deduced that, in the conventional adhesive compositions described in Patent Document 1, polymer particles (such as diene-based core-shell polymers) excessively aggregate in the composition, forming coarse secondary particles, which is related to the decrease in adhesive strength over time. Specifically, the adhesive compositions described in Patent Document 1 have the following problem: the desired adhesive strength may not be achieved over time after manufacturing, and it is preferable to use them quickly after manufacturing.
[0167] Based on this assumption, as described above, the inventors of this application set the proportion of secondary particles with a diameter of 1 μm to 200 μm to 30% or more in the particle size distribution of the secondary particles in the polymer particle aggregate. This provides an adhesive composition with good storage stability and high adhesive strength.
[0168] This specification primarily describes an "adhesive composition" comprising a polymerizable monomer having (meth)acryloyl groups, a free radical polymerization initiator, and polymer particles having the property of swelling due to organic solvents, characterized by a particle size distribution of secondary particles as aggregates of polymer particles. However, the adhesive composition described in this specification can also be used in applications other than bonding, such as as a coating material or an injection agent. In other words, the adhesive composition described in this specification can also be used as a composition with no limitation on its application, a curing composition, or a resin composition.
[0169] This application claims priority based on Japanese Patent Application No. 2021-059627, filed on March 31, 2021, the entire disclosure of which is incorporated herein by reference.
Claims
1. An adhesive composition comprising: Polymerizable monomers having (meth)acryloyl groups; Free radical polymerization initiators; and Polymer particles that swell due to organic solvents, in, In the particle size distribution of secondary particles, which are aggregates of polymer particles in the adhesive composition, as determined by laser diffraction and scattering, the proportion of secondary particles with a diameter of 1 μm to 200 μm is 30% by volume or more. The polymers constituting the polymer particles include diene-based polymers.
2. The adhesive composition of claim 1, wherein, The median particle size D of the secondary particles is determined based on the particle size distribution of the secondary particles. 50 The range is from 1μm to 200μm.
3. The adhesive composition according to claim 1 or 2, wherein, The cumulative 90% diameter D of the secondary particles, calculated based on the particle size distribution of the secondary particles. 90 The range is from 10μm to 500μm.
4. The adhesive composition according to claim 1 or 2, wherein, The volume average particle size of the primary particles of the polymer particles is above 0.01 μm and below 1 μm.
5. The adhesive composition according to claim 1 or 2, wherein, The polymers constituting the polymer particles include (meth)acrylonitrile-butadiene-styrene copolymers and / or (meth)acrylate-(meth)acrylonitrile-butadiene-styrene copolymers.
6. The adhesive composition according to claim 1 or 2, wherein, The polymer particles comprise core-shell polymer particles.
7. The adhesive composition of claim 1 or 2, further comprising an elastomer.
8. The adhesive composition of claim 1 or 2, further comprising a stable radical compound having a stable free radical.
9. The adhesive composition of claim 8, wherein, The stable free radical is a nitric oxide free radical.
10. The adhesive composition of claim 8, wherein, The stable radical compound comprises at least one selected from the group consisting of 1-oxygen radical-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxygen radical and 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine-1-oxygen radical.
11. The adhesive composition of claim 8, wherein, The content of the stable free radical compound is more than 0.001 parts by mass and less than 0.5 parts by mass relative to 100 parts by mass of the polymerizable monomer.
12. The adhesive composition of claim 1 or 2, further comprising a reducing agent.
13. The adhesive composition of claim 12, wherein, The adhesive composition is a two-component adhesive composition consisting of a first agent and a second agent, which are mixed and used immediately before use. The first agent contains the free radical polymerization initiator, and the second agent contains the reducing agent.
14. A joint comprising: First structural component; Second structural component; and A cured body of the adhesive composition according to any one of claims 1 to 13, which bonds the first structural component to the second structural component.
15. A method for manufacturing the adhesive composition according to any one of claims 1 to 13, the method comprising a dispersion step of adding the polymer particles into a container containing the polymeric monomer and stirring to disperse the polymer particles in the polymeric monomer. The temperature of the polymeric monomer at the time of addition is above 0°C and below 40°C.
16. The manufacturing method as described in claim 15, wherein, The stirring is performed using stirring blades at a stirring speed of 300 mm / s or higher.
Citation Information
Patent Citations
JP1972007320U
Modified thermoplastic urethane elastomer modified by core shell polymer
JP2016104834A
Rubber composition for steel cord adhesion and conveyor belt
JP2021059627A
Bonding agent composition for electrode, paste for electrode, electrode and electricity storage device
CN103094582A
Adhesive for low-temperature use
JP1992226579A